Assistance to School Principals in Designing and Managing Independent Curriculum Programs in Elementary Schools - Mustoip, Sofyan; Al Ghozali, Muhammad Iqbal; Rahman, Delfia Ikhlasiah (Inisiatif : Jurnal Dedikasi Pengabdian Masyarakat, 2024)
The implementation of the Independent Curriculum in elementary schools requires principals to be active, visionary leaders in designing and managing programs aligned with its principles. This study evaluated the effectiveness of assistance provided to principals in understanding and implementing the curriculum to improve educational quality and holistic student development. A participatory approach was used to support 10 elementary school principals in Kabupaten Sleman through mentoring sessions. Data were collected via semi-structured interviews to identify challenges, document analysis to assess current practices, and direct observations during sessions. This approach revealed the challenges principals faced in curriculum design and management. Collaborative sessions encouraged dialogue and sharing of strategies. Pre- and post-intervention assessments showed that many principals initially struggled with understanding the curriculum, especially integrating Profil Pelajar Pancasila and designing Project-Based Learning (PBL) activities. Post-assistance, significant improvements were noted in strategic planning, curriculum implementation, and outcome evaluation. The study highlighted the importance of continuous training and collaborative forums for principals. The findings confirm that such assistance effectively equips principals with essential skills, suggesting that sustained professional development is vital for the curriculum’s success and positive impacts on student learning and character. Future research could focus on programs for teachers to support curriculum integration at the classroom level